Genesis of Hematopoietic Tissue and Its Relation with Hemocytes of Litopenaeus Vannamei (Boone, 1931) (Crustacea: Decapoda) - Faiz Muhammad§, Zhi-Feng Zhang*, Ming-Yu Shao, Xiao-Li Shi and Muhammad Shafi (Pakistan Veterinary Journal, 2013)
The Litopenaeus vannamei is a prime aquaculture species and has a worth market value all over the world. In this study, we investigated the genesis and morphology of hematopoietic tissue (HPT) and types of hemocyte based on its morphology and cytochemical feature using histological and histochemical methods. The results revealed that HPT in L. vannamei is not visible histologically in mysis and early two post larvae (P1 & P2), and emerges in P3 which locates in epigastric region. The HPT showed a continuous propagation of cells in successive post larval stages. Four types of cells can be identified in the HPT from adult specimen and mitotic activity is visible in the HPT. The hemocytes have been differentiated into five types and some of these types are co-related with the HPT cells. The cytochemical studies suggested that type I and II cells of hemocytes are PAS positive while scanty presence of prophenoloxidase was observed in type I cells. Similarly the type I cells are Sudan Black B positive and rest of the cells showed weak activity against lipid detective stain. This is the first effort towards genesis of HPT and its relation with circulating hemocytes in L. vannamei.